Pengaruh Karakteristik Entrepreneurial, Jenis Etnis, Jenis Kelamin dan Profesi Orang Tua Terhadap Intensi Berwirausaha Mahasiswa - Chairy, Chairy (Jurnal Manajemen Bisnis, 2011)
Student’s entrepreneurship intention was quite widely researched. However, those studies examined separately factors affecting entrepreneur intention. This study tried to investigate a more comprehansive a more comprehensive favtor which affected the student intention to be entrepreneur. The entrepreneurial characteristics which were investigated consist of innovativeness, need for achievement, locus of control, risk taking provensity, tolarance for ambiguity, and self confidence. This study also research whether the intention to be entrepreneur affected by different ethnic groups, and parental accupation of students (entrepreneurs and non entrepreneurs). Since the number of women entrepreneur in Indonesia is still very limited, this study also investigated how gender differences could be the source of differences in students intention to be entrepreneur. We found that five of six student’s entrepreneurial characteristics significantly affected their intention to be entrepreneur. Futher, this study also revealed that there is no difference in intention to be entrepreneur among students with defferent ethnic groups, parent’s accoupation, and gender